2008
DOI: 10.1007/bf03326034
|View full text |Cite
|
Sign up to set email alerts
|

Modification of thermal and oxidative properties of biodiesel produced from vegetable oils

Abstract: Trans esterification of three vegetable oils, sunflower oil, linseed oil and mixed oils as; sunflowersoyabean and olein were carried out using methanol, and potasium hydroxide as catalyst. The methyl esters of the corresponding oils were separated from the crude glycerol and characterized by physical-chemical methods to evaluate their thermal properties. This methods are determination of densities, cloud points, pour points, flash points, kinematic viscosities, hydrogen/carbon ratios, sulfur contents, ash cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Sometimes they are co-adsorbed with other elements as oxides, hydroxides of Fe, Mn, or may occur in particulate form (Awofolu et al, 2005;Mwiganga and Kansiime, 2005). Heavy metals may enter into aquatic ecosystems from anthropogenic sources, such as industrial wastewater discharges, sewage wastewater, fossil fuel combustion and atmospheric deposition (Linnik and Zubenko, 2000;Campbell, 2001;Lwanga et al, 2003;El Diwani and El Rafie, 2008;Idrees, 2009). Trace elemental concentrations in stream sediment compartments can be used to reveal the history and intensity of local and regional pollution (Nyangababo et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Sometimes they are co-adsorbed with other elements as oxides, hydroxides of Fe, Mn, or may occur in particulate form (Awofolu et al, 2005;Mwiganga and Kansiime, 2005). Heavy metals may enter into aquatic ecosystems from anthropogenic sources, such as industrial wastewater discharges, sewage wastewater, fossil fuel combustion and atmospheric deposition (Linnik and Zubenko, 2000;Campbell, 2001;Lwanga et al, 2003;El Diwani and El Rafie, 2008;Idrees, 2009). Trace elemental concentrations in stream sediment compartments can be used to reveal the history and intensity of local and regional pollution (Nyangababo et al, 2005a).…”
Section: Introductionmentioning
confidence: 99%
“…Bondioli et al (2002) reported that polymers formed during storage of biodiesel in controlled conditions are soluble in oxidized biodiesel, due to its high polarity, and become insoluble only when oxidized biodiesel is mixed with diesel fuel. The physico-chemical characteristics of biobiesel treated with ozonated oil indicated the improvement of the thermal and oxidative stability (El Diwani and El Rafie, 2008).…”
Section: Correlation Between the Chemical Structure Of The Oil And Itmentioning
confidence: 99%
“…2) that ozone dissolution also might be enhanced in presence of UV irradiation. The process of ozone adsorption onto TiO 2 surface and its subsequent decomposition leading to x OH formation is significantly enhanced in UV-assisted TiO 2 -catalyzed ozonation (O 3 /UV/TiO 2 ) (Beltran et al, 2005;El-Diwani and El-Rafie, 2008;Gharbani et al, 2008). Thus, the very small ozone concentrations with O 3 /TiO 2 may be attributed to its adsorption onto TiO 2 surface, while both adsorption onto TiO 2 surface and enhanced decomposition in presence of UV might have resulted to further smaller ozone concentrations with O 3 /UV/TiO 2 .…”
Section: Solution Phmentioning
confidence: 99%